Effects of burn location and investigator on burn depth in a porcine model. Issue 1 (February 2016) - Singer, Adam J.; Toussaint, Jimmy; Chung, Won Taek; Thode, Henry C.; McClain, Steve; Raut, Vivek
Highlights: Reproducibility of animal burn models is critical for their use in research. We compared 2 investigators creating partial thickness burns in porcine model. The mean (SD) depth of injury to blood vessels was 1.8 (0.3) mm. Burns in the non-debrided pig were 0.24 mm deeper than in the debrided pig. Burn depth increased marginally from cephalic to caudal in non-debrided burns. Burn depth was similar with both investigators Abstract: Introduction: In order to be useful, animal models should be reproducible and consistent regardless of sampling bias, investigator creating burn, and burn location. We determined the variability in burn depth based on biopsy location, burn location and investigator in a porcine model of partial thickness burns. Methods: 24 partial thickness burns (2.5 cm by 2.5 cm each) were created on the backs of 2 anesthetized pigs by 2 investigators (one experienced, one inexperienced) using a previously validated model. In one of the pigs, the necrotic epidermis covering each burn was removed. Five full thickness 4 mm punch biopsies were obtained 1 h after injury from the four corners and center of the burns and stained with Hematoxylin and Eosin and Masson's trichrome for determination of burn depth by a board certified dermatopathologist blinded to burn location and investigator. Comparisons of burn depth by biopsy location, burn location and investigator were performed with t -tests and ANOVA as appropriate. Results: The mean (SD) depth of injury to blood vessels (the main determinant of burn progression) in debrided and non-debrided pigs pooled together was 1.8 (0.3) mm, which included 75% of the dermal depth. Non-debrided burns were 0.24 mm deeper than debrided burns ( P  < 0.001). Burn depth increased marginally from cephalic to caudal in non-debrided burns, but showed no statistical differences for these locations, in debrided burns. Additionally, there were also no statistical differences in burn depths from midline to lateral in either of these burn types. Burn depth was similar for both investigators and among biopsy locations. Conclusions: Burn depth was greater for caudal locations in non-debrided burns and overall non-debrided burns were deeper than debrided burns. However, burn depth did not differ based on investigator, biopsy site, and medial–lateral location.